Reproductive Biology of Greenback Mullet, Planiliza subviridis (Valenciennes, 1836) from Segara Anakan Cilacap (Biosaintifika: Journal of Biology & Biology Education, 2023)
Greenback Mullets (Planiliza subviridis) are a commercial commodity and are fished daily in the Segara Anakan Cilacap, although has not been overfished. Continuous and unregulated fishing might harm the Greenback Mullets population. Therefore, sustainable fisheries of this species are still needed. Reproductive biology is among the essential aspect that supports sustainable fisheries. This research aims to obtain information on the reproductive biology of Greenback Mullet in Segara Anakan Cilacap. The research used a survey method with a purposive random sampling technique. The observed parameters were the gonad maturity stage, gonad maturity index, and fecundity. The data were analyzed descriptively. The female individuals have gonad maturity stages III and IV, gonad maturity stage was 16.81±2.59 and 16.92±2.51, and fecundity was 37,208-183,661 and 38,468 - 272,835 in August and October, respectively. Conversely, male individuals have a low gonad maturity stage and gonad maturity index. Based on the data, Greenback Mullets in the Segara Anakan estuary have maximum gonad maturity stage, gonad maturity index, and fecundity in August and October, while in February they were in early gonadal development. These data are essential for sustainable fisheries management in the Segara Anakan estuary Cilacap, Central Java, especially for Planiliza subviridis.